Ilmu 'Arudh Sebagai Sistem Pengetahuan: Pendekatan Epistimologis Dalam Studi Bahasa Arab - Lydia Ni’matul Mu’tamaroh; Intan Nadiroh; M. Yunus Abu Bakar (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This article discussed ʿIlm al-ʿAruḍ as a system of knowledge within Arabic language studies through an epistemological approach. Prior to this study, ʿIlm al-ʿAruḍ had often been understood merely as a technical tool for analyzing poetry, whereas it actually possessed a structured set of concepts, working methods, and clear criteria of validity for determining the correctness of wazan (metrical patterns) and the regularity of rhythm in Arabic poetry. This study employed a qualitative approach with a library research design, using descriptive–analytical analysis. The findings indicated that ʿIlm al-ʿAruḍ functioned as a scientific instrument for verifying metrical and rhyming patterns, which demonstrated that it held not only aesthetic value but also academic significance within the scholarly tradition of Arabic studies. From an epistemological perspective, the discussion showed that ʿIlm al-ʿAruḍ had identifiable sources of knowledge, analytical procedures, and mechanisms of verification that could be academically justified. Furthermore, the study found that ʿIlm al-ʿAruḍ remained relevant in contemporary Arabic language education when taught contextually and connected to modern linguistic studies, particularly phonology and linguistic rhythm. Therefore, it was concluded that ʿIlm al-ʿAruḍ deserved to be positioned as an essential component of the structure of Arabic linguistic sciences, both for strengthening the understanding of Arabic literature and for developing deeper linguistic competence.